2016
DOI: 10.3892/etm.2016.3138
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil exhibits osteoprotection in ovariectomized rats without estrogenic effects

Abstract: Abstract. The present study was designed to evaluate the effect of olive oil on bone and uterus in ovariectomized rats. A total of 34 surgically ovariectomized or sham-operated virgin Sprague-Dawley rats were divided into four groups: i) Sham-operated control rats (sham group); ii) Ovariectomized rats (OVX group); iii) Olive oil-supplemented ovariectomized rats (olive group); and iv) Diethylstilbestrol-supplemented ovariectomized rats (E 2 group). At 12 weeks following left ventricular blood sacrificed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Radiotherapy has significant efficacy in treating many tumors, but resistance to radiotherapy is one of the critical factors affecting the prognosis of tumors [ 11 , 12 ]. Ovarian cancer is one of the most common gynecologic malignancies, with a high incidence and mortality rate, and is a severe health risk for women worldwide [ 13 , 14 ]. In response to the limited therapeutic options, radiotherapy has become a standard treatment [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has significant efficacy in treating many tumors, but resistance to radiotherapy is one of the critical factors affecting the prognosis of tumors [ 11 , 12 ]. Ovarian cancer is one of the most common gynecologic malignancies, with a high incidence and mortality rate, and is a severe health risk for women worldwide [ 13 , 14 ]. In response to the limited therapeutic options, radiotherapy has become a standard treatment [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an increase in oestrogen levels in the experimental groups was recorded when compared to the control animals. This has been shown in the work of Zheng, Huang, Zheng, & Li, (2016). They observed that the oral administration of olive oil and garlic increased the serum oestrogen concentration when compared to the group exposed to oestradiol.…”
Section: Discussionmentioning
confidence: 55%